Respon Upah Buruh Tani terhadap Harga Gabah Kering Panen (GKP) di Indonesia Tahun 2009-2020 - Helbawanti, Octaviana; Suyudi, Suyudi; Nuryaman, Hendar (Universitas Veteran Bangun Nusantara, 2022)
One of the factors determining the price of unhulled rice (GKP) as is the labor cost which is represented by the wages of farm laborers. Vector Autoregressive (VAR) estimated the positive response of GKP prices due to changes in nominal farm labor wage. Price of hike in farm labor wages caused the increase the proportion of labor cost in farm production costs. Price regulation implemented by government for rice as a staple food could be considered by producers to controll the costs of production factors , one of them was because labor cost determined the profits of paddy farming. Changes in GKP prices affected the supply and demand for labor, the number of workers employed by producers and labor expectations in obtaining income at the paddy farming. The relation of the price of GKP and nominal labor wage was depicted in two-way causality using Engle-Granger Causality. Keywords: Farm Worker, Unhulled Rice, Wage